Comparative analysis of UI construction and performance in android and flutter frameworks / Zou Donglan ... [et al.] - -, Zou Donglan; Darus, Mohamad Yusof; Abdul Aziz, Maslina; Zambri, Suzana (Universiti Teknologi MARA Press (Penerbit UiTM), 2024)
This article examines the process of building user interfaces (UI) using two leading mobile application development tools: Android and Flutter. By developing common login interfaces, the UI construction between these platforms was compared and contrasted. The study highlights key differences in UI elements, design paradigms, and performance metrics, offering a comprehensive analysis. A detailed experimental plan to assess and compare UI development in Flutter and Android was designed, followed by performance evaluations based on metrics such as application size, runtime speed, and memory usage. The findings aim to help beginners quickly grasp and master these tools. Furthermore, the implications for developers, particularly regarding code complexity, reusability, and the overall development experience were discussed. This research contributes to the ongoing discourse on mobile app development best practices, helping guide tool selection for specific project requirements.